2015
DOI: 10.1007/s11739-015-1279-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute deep vein thrombosis (DVT) of the lower limbs in a 32-year-old man with chronic hypoplasia of the inferior vena cava (HIVC) without risk factors

Abstract: The anomalies of the inferior vena cava (IVC) have an incidence between 0.2 and 1 % in the general population [1]. The normal average diameter of the IVC is 17.5 mm (up to 25 mm maximum) and the spectrum of anatomical abnormalities of the IVC (e.g., absence or interruption of the vessel or variation in diameter) can be responsible for serious hemodynamic effects to the venous circulation of the lower limbs (i.e., venous stasis), and be a risk factor for the development of deep vein thrombosis (DVT). The associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Since our study showed an important significance on public health due to the high risk of venous thromboembolic disease (45), it has a limit concerning the number of recruited subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Since our study showed an important significance on public health due to the high risk of venous thromboembolic disease (45), it has a limit concerning the number of recruited subjects.…”
Section: Discussionmentioning
confidence: 99%